The association between an individual’s development of non-communicable diseases and their spouse’s development of the same disease: the Longitudinal Survey of Middle-aged and Elderly Persons - Ukai, Tomohiko; Tabuchi, Takahiro; Iso, Hiroyasu (Environmental Health and Preventive Medicine, 2025)
Background: Studies have shown that married couples often share similar lifestyles, as well as lifestyle-associated conditions such as diabetes, hypertension, and hyperlipidemia. This study aims to prospectively investigate the association between an individual’s development of a non-communicable disease and the subsequent development of the same condition in their spouse.Methods: This population-based cohort study utilized 12 waves of annual prospective surveys from 2005 onwards in Japan, with a discrete-time design. A total of 9,417 middle-aged couples (18,834 participants; discrete-time observations = 118,876) were included. Each participant whose spouse had developed one of six conditions was propensity score-matched with five controls whose spouses had not been diagnosed with the condition: diabetes [n = 1374 vs n = 6870], hypertension [n = 2657 vs n = 13285], hypercholesterolemia [n = 3321 vs n = 16605], stroke [n = 567 vs n = 2835], coronary heart disease (CHD) [n = 1093 vs n = 5465] or cancer [n = 923 vs n = 4615]. Using conditional logistic regression, we assessed participants’ development of the same condition within three years following their spouse’s diagnosis.Results: Participants whose spouses had developed diabetes, hypertension, hypercholesterolemia, or CHD were more likely to develop the same condition within three years. The odds ratios (ORs) and 95% confidence intervals (CIs) were: 1.96 (1.53–2.50), 1.20 (1.06–1.36), 1.63 (1.47–1.81) and 1.43 (1.05–1.95), respectively. No significant associations were observed in stroke [1.69 (0.80–3.58)] or cancer [1.08 (0.75–1.54)].Conclusion: Spouses of individuals recently diagnosed with certain metabolic conditions are at a higher risk of developing those conditions themselves. These findings may provide valuable guidance for targeting and personalizing chronic disease screening and prevention efforts.